DESTINATION POSITIONING AND GENERATION Z LOYALTY IN TOURISM: THE MEDIATING INFLUENCE OF DESTINATION EXPERIENCE AND DESTINATION IMAGE - Lestari, Resa Dwi Lestari (Universitas Islam Negeri Alauddin Makassar, 2024)
This research investigates the interaction between destination positioning, destination experience, destination image and loyalty among Generation Z travelers, who have emerged as a significant force in the tourism industry. Given their distinct preferences influenced by digital and and social media influences, this research aims to analyze how destination experience and destination image mediate the relationship between destination positioning and Generation Z loyalty. Using non-probability purposive sampling technique, data was distributed through a survey to 200 Generation Z respondents in Indonesia. Structural Equation Modeling with AMOS was used to examine the relationships between variables in the study. Discovering revealed that a positive brand experience significantly improves destination image, which in turn fosters loyalty among young travelers. The implications of these insights suggest that tourism stakeholders should innovate their marketing strategies to create immersive experiences that align with Generation Z values, ultimately driving engagement and repeat visits in a competitive market.